The impact of health wallets in user-centric healthcare - Mateus, D.; Martins, A.; Correia, R. (Proceedings Euroma 2025, 2025)
Health Wallets (HWs) mark the next shift toward user-centric healthcare, using FHIR and Blockchain. The paper aims to synthesize existing academic knowledge on HWs through a Systematic Literature Review (SLR), complemented by empirical insights from a survey (n=33), identifying promising benefits, challenges, support technologies, and requirements of the use of HWs. Findings show that adoption faces challenges in privacy, interoperability, and change management. However, HW solutions translate continuous improvement in healthcare operations by streamlining processes while understanding stakeholders and overcoming resistance, relying on co-value creation to outweigh these challenges.